Ressignificação de temas geradores na Educação Física da EJA: das situações-limite aos inéditos viáveis - Marcelo Luiz de Souza (2023)
This study is affirmed by my political-pedagogical commitment to Youth and Adult Education (YAE) as popular education for working-class learners. The heterogeneity of the students is one of the most noticeable characteristics in this teaching modality, from different points of view. EJA students attribute differentiated senses and meanings to learning and practices. In this sense, the educational process in this teaching modality is not merely a transmission of passive contents disconnected from reality. The educator needs to get closer to the learner, with a sensitive and sincere listening, getting to know their reality, understanding the limiting situations that involve them and the context, to then think of a pedagogical proposal that leads to viable novelties. Since Physical Education became compulsory in EJA, many changes have occurred, however, we still have two fights to fight: first, the defense of the modality as a universal right, and second, the concern with the effectiveness of the Physical Education curricular component appropriate to the characteristics of the public. This study presents a re-signified pedagogical proposal, based on my experiences with generating themes, grounded on my historicity as a researcher-teacher. It is qualitatively based on the research-teaching field and supported by a bibliographic research from the analysis of theoretical references to elaborate a proposal in the light of contemporaneity in Physical Education for EJA. In it, we contemplate the different subjects, their identities, differences, subjectivities, culture, and territory. The experiences narrated throughout this study were developed with EJA from two different realities, and are: Capoeja - thematization of capoeira as a cultural body practice; Indigenous peoples' body practices: body - culture - inclusion - citizenship; "Bola de meia, bola de gude" - there is a past in my present. With this study, I reinforce that it is the transforming and emancipatory action through the daily pedagogical praxis of being in the world with the possibility of - through dialogue - potentiating democratic, plural, and adequate practices to the reality of the EJA subjects in order to critically think the world we live in. What is ahead of us? I follow Nietzsche's propositions, who oriented us to live the present with the will to power, creative and destructive, but always as a becoming (a feasible unseen in Paulo Freire's work), in an eternal return to itself. This is how EJA is - EJA is struggle, EJA is the right, EJA is the present!